Modular strategy with autologous bioreactor: a potential way for organ engineering - Qingfeng Bai; Hai Tang; Yi Chen; Ziyin Pan; Weikang Lin; Lei Wang; Yulong Hu; Boyu Xu; Minglei Yang; Guofang Zhao; Weiyan Sun; Yong He; et al. (International Journal of Extreme Manufacturing)
Bioengineered organs have been seen as a promising strategy to address the shortage of transplantable organs. However, it is still difficult to achieve heterogeneous structures and complex functions similar to natural organs using current bioengineering techniques. This work introduces the methods and dilemmas in organ engineering and existing challenges. Furthermore, a new roadmap for organ engineering, which uses a modular strategy with autologous bioreactors to create organ-level bioengineered constructions, is summarized based on the latest research advances. In brief, different functional modules of natural organs are constructed in vitro , and autologous bioreactors in vivo are utilized to facilitate inter-module assembly to form a complete bioengineered organ capable of replacing natural organ functions. There are bioengineered organs, such as biomimetic tracheas, which have been successfully fabricated following this roadmap. This new roadmap for organ engineering shows prospects in addressing the shortage of transplantable organs and has broad prospects for clinical applications.